(untitled) (Journal of the College of Education for Women, 2019)
Japans expansionist policy begins (Phase I) after the Chinese- Japanesewar in 1895 until end of the Washington conference in 1922 marine. Thereforesought to implement the expansion program from the effect that get it afterChinese- Japan war 1894-1895, and the Russo- Japanese conditions of thefirst world war to complete its expansion program through the provision oftwenty- one demands and imposed on china.In (1916-1917) it was signed a secret agreement with Allied power, thatincluding the German concessions in the far East to Japan legally has alreadyreceived official recognition from the international community.In sum, the Japan during its period of expansion that has becom the firstAsian power that humiliated the European and Asian powers also and was thefirst defeat the power of Estern European power in modern history during thewar (Russian- Japanese) and thus became Japan after (world war I) and oneof the big five forces in the world.In the expansionist occupation of Manchuria in (1931 phase II), thatfinished by the end of world war II in 1945, because the tendency of Japaneseexpansionism is not ended with signing of treaties and U. S. Navy in 1922, butwas temporarily interrupted, the arrival of military leaders power thatrepresentative of Gen. (Thanak j. j) in 1927In the conjunction of the effect of economic crisis and the need forJapanese launched the largest expansion program in 1931 with the secondworld war. In 1939 Japan took the opportunity to apply its new program in thefar east in 1938.But in 1941, the largest mistake that have been done by the Japanese militarywhen it was attains the U. S. Navy that tipped the balance in the side of thestate of the Allies and make the Japan loss of it had led the world after the warinstead of the second scientific American and the united stats overturned thepalance of power that now exists.At the end we can say that the Attempts of the Japanese expansionistpolicy, reached to the aspiration for world supremacy or at least nearuniversal.Also, the end of the days that Japan signed out that make the two power ofthe two military, ground Navy forces, that make it defatted and lose the empireand returned from where it began.